2017
DOI: 10.1016/j.clgc.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A Walking Intervention Among Men With Prostate Cancer: A Pilot Study

Abstract: Background Men diagnosed with prostate cancer have increased risk for disease progression, cardiovascular events and impairments in quality of life. This pilot study evaluated the feasibility of a randomized walking group intervention to improve quality of life, circulating biomarkers, and morbidity among men with newly diagnosed prostate cancer. Methods Men were recruited at Örebro University Hospital, Sweden and randomized to an 11-week walking group intervention (n=21) or usual care (n=20). The interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…It is known that walking improves our defense against diseases and contributes to health improvement [ 15 , 16 , 17 , 18 , 19 ]. Walking improves health and the Ministry of Health, Labor and Welfare of Japan supports the current physical activity guidelines [3] .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that walking improves our defense against diseases and contributes to health improvement [ 15 , 16 , 17 , 18 , 19 ]. Walking improves health and the Ministry of Health, Labor and Welfare of Japan supports the current physical activity guidelines [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile only 6.7% of control group participants reported low levels of support pre-and post-intervention. Perceptions of both partner support and patient self-confidence in performing sexual activities have been shown to significantly affect sexual health in men with prostate cancer [10,55] which may help to explain the finding by Pernar et al [38].…”
Section: Exercise and Combined Vascular And Sexual Health In Prostatementioning
confidence: 85%
“…An 11-week group-based walking (once per week) study by Pernar et al [38] did not lead to significant between-group improvements in SBP, DBP, or sexual function as assessed by a visual analogue scale with the associated question "Do you have problems with your sex life?". Interestingly, this study observed a non-significant within-group reduction in sexual function in the walking group (+25.8%) and non-significant within-group improvement in the usual care group (−28.6%).…”
Section: Exercise and Combined Vascular And Sexual Health In Prostatementioning
confidence: 92%
See 1 more Smart Citation
“…44 Numerous trials on exercise in patients with prostate cancer using such modalities as aerobic exercise, resistance training, and walking exercise regimens have shown benefits for improving cardiovascular health, reducing proinflammatory cytokines, and mitigating the adverse effects of fatigue from ADT. 13,[45][46][47][48][49] The ENGAGE trial demonstrated the feasibility and tolerance of a community-based exercise training program that was consistent with the American Cancer Society prostate cancer survivorship care guideline recommendation of at least 150 minutes of physical activity per week, with both supervised and unsupervised sessions for men on ADT. 50 Exercise, along with daily nutritional supplementation of at least calcium 1,200 mg and vitamin D 600 IU to 1,000 IU, also helps to minimize bone loss and osteoporosis as a result of treatment with ADT.…”
Section: Management Of Patients Before and During Adtmentioning
confidence: 99%